Will the specialization or involution thesis hold for smallholder mixed farming systems of harar highlands?: rethinking research direction and intervention options for sustainable smallholder agriculture development in Ethiopia - Kassa, H.; Assefa, M. (St. Mary's University, 2010)
This study explored trends of farming systems and livelihood options over time, and examined changes in livestock inventory in relation to changes in farm size and socio-economic status of smallholder farmers in the Harar Highlands of Ethiopia. Three districts with different rural population densities (low, medium, and high) were identified. Community level information was collected using participatory research methods. Then a formal survey was administered on 225 households randomly selected from the three districts and belonging to three well-being categories (poor, medium, and well-to-do). Both one-way and two-way ANOVA were used to analyse data. The results showed that farmers changed their livestock inventory (species composition and number) as farm sizes declined, moving mainly from ruminants to non-ruminants. Total livestock holdings varied significantly across districts and well-being groups (P<0.001). Livestock holdings per household of all species, except donkeys, declined as rural population density increased and augmented with improvements in socio-economic status. The number of livestock per unit area of cultivated land, however, increased significantly (P<0.001) with rural population density, except for sheep and goats. Though livestock holdings declined as farm sizes shrank with significant variations across districts, farmers continued to rear livestock. This was observed even when land sizes declined to less than a hectare per household. In the most populated district, the average livestock holding was 2.21 TLU per household. The conceptual framework, which assumes that as land resources dwindle mixed farming systems will have to specialise into crop or livestock farming units or could face involution, does not seem to be holding for the Harar Highlands of Ethiopia, at least in the near future. Its validity in similar areas will have to be re-examined. Therefore, research priorities and development initiatives in tropical smallholder mixed farming systems must consider the continued importance of the crop-livestock integration even when farm sizes decline significantly. The options of generating crop-or livestock-focused technologies that assume specialisation must be revisited and varieties and breeds or species and cropping and livestock systems that allow improvements for further intensifications of mixed farms must be identified and promoted.